Population structure and dispersal patterns in Scottish Golden Eagles Aquila chrysaetos revealed by molecular genetic analysis of territorial birds. (14th August 2015) - Ogden, Rob; Heap, Elizabeth; McEwing, Ross; Tingay, Ruth; Whitfield, D. Philip; Voelker, Gary
<x xml:space="preserve">Abstract</x> Conservation management of species distributed across fragmented habitats requires consideration of population genetic structure and relative levels of genetic diversity throughout the relevant geographical range. The Golden Eagle Aquila chrysaetos is monitored within Scotland to ensure its survival in the face of land‐use pressure, persecution and future climate change. In this study we constructed DNA profiles for 271 individual birds using a collection of over 1600 moulted feathers collected from 148 territories, representing 34% of known Scottish territories in the largest population genetic study of Golden Eagles undertaken to date. The results, based on data from 10 nuclear microsatellite loci, revealed previously unreported genetic structure between the islands of the Outer Hebrides and the rest of Scotland (FST = 0.03), together with evidence of reduced genetic diversity in the Outer Hebridean population compared with mainland Scotland. Analysis of gene flow supports a hypothesis of limited, predominantly male‐mediated, dispersal from the Outer Hebrides to mainland Scotland. The persistence of this pattern is discussed with respect to variation in population density and persecution pressure across Scotland. A finding of non‐random mating within the Outer Hebrides is interpreted as evidence of natal philopatry that was revealed by more intensive sampling in these islands, and is likely to be accentuated by the apparent degree of isolation of the islands from the rest of Scotland.